Criminal Acts Against the Judicial Process (Contempt of Court) According to the New Criminal Code about the Right to Immunity of Advocates in Court - Agustini Andriani (Publikasi Indonesia, 2024)
The birth of the new Criminal Code brought nuances of renewal in the world of justice in Indonesia. However, it also caused upheaval and differences of opinion regarding regulating several aspects of criminal law, including regulating Criminal Acts Against the Judicial Process (Contempt of Court). The regulation of Contempt of Court actions in the new Criminal Code raises pros and cons in society, including advocates who often intersect with the judicial world. The existence of several articles regulating multi-interpretive contempt of court actions is considered to threaten the existence of the Advocate's Right to Immunity in Court. This study aims to analyze the regulation of the Contempt of Court criminal acts regarding the right to immunity of advocates in Court. The research method used is normative legal research using an analytical descriptive approach. This study found that the articles of Contempt of Court in the new Criminal Code, which are multi-interpretive, can limit the space for advocates to express opinions and defend themselves before the court. If these articles are not interpreted properly and correctly, they can become a medium for criminalization by specific individuals against advocates in court.